2019
DOI: 10.1038/s41385-018-0093-5
|View full text |Cite
|
Sign up to set email alerts
|

The emergence of pathogenic TNF/iNOS producing dendritic cells (Tip-DCs) in a malaria model of acute respiratory distress syndrome (ARDS) is dependent on CCR4

Abstract: Malaria-associated acute respiratory distress syndrome (MA-ARDS) and acute lung injury (ALI) are complications that cause lung damage and often leads to death. The MA-ARDS/ALI is associated with a Type 1 inflammatory response mediated by T lymphocytes and IFN-γ. Here, we used the Plasmodium berghei NK65 ( PbN )-induced MA-ALI/ARDS model that resembles human disease and confirmed that lung CD4 + and CD8 + T cells predomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 48 publications
(55 reference statements)
3
39
1
Order By: Relevance
“…Thus, HOCl, tyrosyl radical, NO 2 and MPO are collectively involved in the production of inflammatory cytokines (Aratani, ). It is well known that stressed condition is positively correlated with the inflammation, and TNF‐α is one of the extensively studied pro‐inflammatory cytokines having a well‐defined gonadal toxic profile in clinical and pre‐clinical findings (Galvão‐Filho et al, ; Veny, Virgen‐Slane, & Ware, ). In the current study, administration of CP 200, significant elevation in MPO expression and increased TNF‐α was observed in the testis and epididymis (Figure and Figure ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, HOCl, tyrosyl radical, NO 2 and MPO are collectively involved in the production of inflammatory cytokines (Aratani, ). It is well known that stressed condition is positively correlated with the inflammation, and TNF‐α is one of the extensively studied pro‐inflammatory cytokines having a well‐defined gonadal toxic profile in clinical and pre‐clinical findings (Galvão‐Filho et al, ; Veny, Virgen‐Slane, & Ware, ). In the current study, administration of CP 200, significant elevation in MPO expression and increased TNF‐α was observed in the testis and epididymis (Figure and Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…related with the inflammation, and TNF-α is one of the extensively studied pro-inflammatory cytokines having a well-defined gonadal toxic profile in clinical and pre-clinical findings(Galvão-Filho et al, 2019;Veny, Virgen-Slane, & Ware, 2018). In the current study, administration of CP 200, significant elevation in MPO expression and increased TNF-α was observed in the testis and epididymis(Figure 2andFigure 3).…”
mentioning
confidence: 99%
“…Five-micrometer sections from fixed, paraffin-embedded whole lung were stained using hematoxylinand-eosin and examined by light microscopy. The scoring system was based on one that was previously report (27), briefly: 0 = no injury (apparently normal tissue); 1 = discrete and slight, when the lesion occupies <25% of the tissue; 2 = moderate when the lesion occupies 25-50% of the tissue; and 3 = intense, a severe injury with diffuse or focal inflammation around all structure of biopsy occupying more than 50% of the tissue.…”
Section: Histology and In Situ Cell Death Detection Of Lung Tissuementioning
confidence: 99%
“…In our earlier studies, we found that MO-DCs are an important source of active caspase-1, IL-1β and have a pathogenic role in ECM and acute respiratory distress syndrome in malaria (MA-ARDS) models 18 , 44 , 49 . To address the importance of inflammatory caspases in ECM, RNA was extracted from MO-DCs (CD11b + F4/80 + CD11c + DC-Sign + MHC II + , purity >97%) highly purified from spleens of control and infected mice (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%